Antidesma bunius aqueous crude extract promotes cell death via modulation of redox-sensitive and autophagy-associated genes in HCT 116 human-derived colorectal cancer cells - Benigno, Sol Joaquin; Oyong, Glenn; Licayan, Josafat John; Sumayao, Rodolfo (Archives of Biological Sciences, 2020)
Paper description: Antidesma bunius fruit exhibits antioxidant properties. Its anticancer activities remain underexplored. We investigated the effects of Antidesma bunius fruit aqueous extract (A. bunius ACE) on the redox status, mitochondrial integrity and expression of genes associated with oxidative stress (the state of redox imbalance), and autophagy (a cellular ‘housekeeping’ process) in the colorectal cancer cell line, HCT 116. A. bunius ACE reduced the oxidative stress and enhanced mitochondrial integrity of HCT 116 cells, accompanied by upregulation of genes associated with oxidative stress and autophagy. These changes point to a potential anti-cancer mechanism and underscore the therapeutic potential of A. bunius fruits. Abstract: Antidesma bunius fruit was previously shown to exhibit antioxidant properties, but its anticancer activities remain underexplored. We hypothesized that the phytochemicals in this fruit can influence mitochondrial integrity and can modulate stress-responsive genes in cancer cells. The present study investigated the effects of A. bunius fruit aqueous crude extract (A. bunius ACE) on the viability, redox status, and mitochondrial transmembrane potential (MTP) using a colorectal cancer cell line, HCT 116. The expression of key genes associated with oxidative stress and autophagy was also determined. Treatment of cells with A. bunius ACE resulted in a ~27% reduction in viability, coupled with a marked decrease in oxidative stress index by ~59%. This was accompanied by the upregulation of NRF2 and NRF2-dependent genes. MTP increased ~3-fold in response to A. bunius ACE. The expression of BECLIN1, ATG5, and LC3 genes also increased. Our results indicate that the phytochemicals in A. bunius fruits enhance mitochondrial integrity and modulate the expression of stress-responsive genes, which may be responsible for the mitigation of oxidative stress in cancer cells. These alterations may be involved in the cascade of events leading to cancer cell death effected by A. bunius. https://doi.org/10.2298/ABS200703037B Received: July 3, 2020; Revised: August 24, 2020; Accepted: August 25, 2020; Published online: August 27, 2020 How to cite this article: Benigno SJ, Oyong G, Licayan JJ, Sumayao R Jr. Antidesma bunius aqueous crude extract promotes cell death via modulation of redox-sensitive and autophagy-associated genes in HCT 116 human-derived colorectal cancer cells. Arch Biol Sci. 2020;72(3):433-43.